Factor Influencing The Utilization of Pay Later Payment Option on Traveloka - Sofyan, Mahardhika Dwi Ananta; Aprianingsih, Atik (Journal of Business and Management, 2020)
Abstract. This study examined factors that influencing intention to use of Pay Later feature on Traveloka in Indonesia. The Theory of Planned Behavior was adopted as a theoretical foundation of the study. A total of 400 valid and reliable responses collected using questionnaires were used for data analysis. The data were analyzed using Multi Linear Regression (MLR) approach and measured by Path analysis. The findings depict that attitude, subjective norm, and perceived behavioral control have significant influence on continuance behavioral intention. The study provides a number of useful implications for scholars and practitioners which could be used to enhance and provide sustainable Pay Later services to users.Keywords: Customer Intention, Path Analysis, Pay Later, Theory Planned Behavior (TPB)